2003
DOI: 10.1023/b:jopc.0000005457.29475.d7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gp17 Glycoprotein and Characterization of Prostatic Acid Phosphatase (PAP) and Carboxypeptidase E (CPE) Fragments in a Human Seminal Plasma Fraction Interacting with Concanavalin A

Abstract: The decapacitating fraction of human seminal plasma, which strongly interacts with concanavalin A, is constituted by high mannose-type N-linked glycoproteins, most of them of less than 44 kDa. Each component with apparent molecular mass of 30, 18, and 17 kDa respectively, as judged by SDS-PAGE, was submitted to "in gel" digestion with trypsin followed by HPLC separation of the peptides and sequencing. They were characterized at microscale as gp17, an aspartyl protease that possibly contributes to liquefaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…MS/MS analysis of other protein spots also identified lower molecular weight forms of PAP (spots 11–13); along with carboxypeptidase E (spots 9 and 10) and transthyretin amyloidogenic variants (spots 14 and 15). Presence of lower molecular weight fragments of PAP, together with carboxypeptidase E in the seminal plasma has also been reported by Marquínez et al [32]. Similarly, naturally occurring fragments of PAP are found to be present as amyloid fibrils in the seminal plasma [33].…”
Section: Discussionsupporting
confidence: 68%
“…MS/MS analysis of other protein spots also identified lower molecular weight forms of PAP (spots 11–13); along with carboxypeptidase E (spots 9 and 10) and transthyretin amyloidogenic variants (spots 14 and 15). Presence of lower molecular weight fragments of PAP, together with carboxypeptidase E in the seminal plasma has also been reported by Marquínez et al [32]. Similarly, naturally occurring fragments of PAP are found to be present as amyloid fibrils in the seminal plasma [33].…”
Section: Discussionsupporting
confidence: 68%
“…Chromatography on concanavalin A (ConA)-Sepharose column (22 by 1 cm; Amersham Pharmacia, Uppsala, Sweden) was performed as previously described (32,34). The bed volume of the column was 5 ml, and the flow rate was 12 ml/h.…”
Section: Hiv-1 Trans-infection Assaysmentioning
confidence: 99%
“…Con A recognizes high mannose, hybrid and biantennary complex-type N-glycans [28]. Also, Marquínez et al had demonstrated in their research that the human seminal plasma Con A-interacting fraction shows decapacitating activity [18]. Thus, identification of Con A binding protein fraction of human seminal plasma is of paramount importance for better understanding of fertility related physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the previous studies have successfully applied Con A lectin affinity chromatography to enrich and isolate glycoproteins [14][15][16][17]. More captivatingly, Con A-interacting fraction of human seminal plasma shows decapacitating activity [18]. Thus, the study towards isolation and identification of various proteins of this fraction is of vast importance and may help us in better understanding of fertility related processes.…”
Section: Introductionmentioning
confidence: 99%